Gênese, evolução e geomorfologia das ilhas e planície de inundação do alto Rio Paraná, Brasil - Leli, Isabel Terezinha [UNESP] (2015)
This study aims to look at the genesis, evolution, morphology and sedimentology of islands and floodplain of the Upper Paraná River, Brazil. The study reach encompasses 235 km of river limited by the Porto Primavera Dam, in the Parana, São Paulo and Mato Grosso do Sul State border and the reservoir of the Itaipu, near the city of Guaíra, PR. Satellite images, vibro-corer drillings, facies and grain-size analysis, dating, morphological mapping and hydrological studies were performed for this study. In this reach, the river has an anabranching pattern with 265 islands varying in size (from tens to thousands of meters), age (from the end of Pleistocene to the Present) and morphology. Intra- and extra-channel processes form islands and their deposits vary according to the depositional environments involved. In the first case, the central bar islands are formed, in the case of extra-channel processes, are formed the islands excised from floodplain. Both types of islands can grow by attaching lateral and frontal bars and form composite central bar and composite islands excised. The Mutum Island is a composed central bar island whose deposits are formed by sandy channel deposits at the base, followed by mud and fine sand deposits of abandoned channels, lakes and swamp, and muddy red soil in the top corresponding to terrestrial conditions. The island is about 8,200 years BP and enlarged by lateral (94 mm/year) and vertical (0.06 mm/year) accretion. The Mutum is a typical island within the study reach whose formation processes have been at work since the beginning of the Holocene. The Bandeirantes and Grande Islands are typical islands excised from floodplain. In this case, they are very large islands (> 250 km2) formed during the Upper Pleistocene and Lower Holocene (14,620 to 5,520 years BP) under hydrosedimentological and geomorphological conditions different from the present. The floodplain forming process in this period was the attachment ...